Activating molybdenum disulphide basal-plane for enhanced hydrogen evolution reaction through direct defect engineering - Hao Liu; Haiyang Chu; Shuhua Zhao; Siyu Shang; Chenxi Zhou; Deying Wen (Results in Chemistry)
Hydrogen evolution reaction (HER) is a promising method for hydrogen production, but existing catalysts often face challenges like high overpotentials and slow kinetics. Here, the platinum (Pt) doped hexagonal molybdenum disulphide (Pt@Ar-2H MoS₂) catalyst was obtained by the treatment of argon ion bombardment and xenon lamp irradiation methods. With a low overpotential of 52 mV at 10 mA cm−2, low Tafel slope of 77.4 mV dec−1 and low charge transfer resistance (20 Ω), the Pt@Ar - 2H MoS₂ catalyst exhibits good electrochemical HER activity.The Pt@Ar-2H MoS2 catalyst was obtained by the treatment of argon ion bombardment and xenon lamp irradiation methods. With a low overpotential of 52 mV at 10 mA cm−2, low Tafel slope of 77.4 mV dec−1 and low charge transfer resistance (20 Ω), the Pt@Ar-2H MoS2 catalyst exhibits good electrochemical HER activity.